A greener approach towards double heteroarylation of N, O and S nucleophiles: synthesis of bioactive polynuclear fused N-heteroarenes1. Issue 91 (9th October 2015) - Nikumbh, Satish P.; Raghunadh, Akula; Murthy, V. Narayana; Jinkala, Rajesh; Joseph, Suju C.; Murthy, Y. L. N.; Prasad, Bagineni; Pal, Manojit
<x xml:space="preserve">Abstract</x> We report first general and common strategy for double heteroarylation of N, O and S nucleophiles leading to polynuclear N-heteroarenes.